The Role of the Teacher’s Vocation in the Efficiency Building of an Education System - Paurienė, Giedrė; Žemaitaitytė, Irena (Acta Paedagogica Vilnensia, 2020)
The article analyzes the experiences determined by biographical circumstances that encourage individuals to choose the profession of a teacher in the pursuit of their vocation. Based on people’s biographies, it can be argued that many separate stages of human life, viewed as a whole, provide a meaningful context that can help understand the phenomenon of vocation and reveal its links to the development of professional competencies and to the efficiency of the educational system. The research usually explains the efficiency of an educational organization through pedagogical, managerial, economic and institutional aspects and defines it by qualitative characteristics that are related to the acquisition of knowledge, skills, results achieved by children, efficient use of resources, and the improvement of the teaching process. The aim of the article is to reveal a person’s vocation to become a teacher as a condition, on the one hand, leading to the pedagogical educational process through informal learning, and, on the other hand, making the educational system more efficient. The analysis and results of the qualitative research data are based on the abductive theory construction according to Peirce and the methodology of the Grounding Theory according to Strauss / Corbin. The research revealed that the choice of pedagogical profession and the perception of vocation are evoked by biographical circumstances. The pedagogical potential noticed and mentioned by the close people as well as the preferences for certain activities from childhood and the perception of one’s needs become a basis for the further development of existing competences. Thus, when a competent educator who experiences strong dedication to an educator’s profession gives lessons in an educational institution, the effective and purposeful activity of the educator interacts with the efficiency building of the education system.